Design, comparison and experimental evaluation of non-overlap winding radial flux permanent magnet hub drives for electric vehicles - Rix, Arnold Johan (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD (Electrical and Electronic Engineering))--University of Stellenbosch, 2011.